Conflicting words: the Peace Treaty of Münster (1648) and the political culture of the Dutch Republic and the Spanish Monarchy - Manzano Baena, Laura (Avisos de Flandes, 2011)
Portraying the political culture of both the Catholic Monarchy and the United Provinces, this work analyses the views held in both territories concerning the points which were discussed in pamphlets and treatises published during the peace negotiations. It also traces the origin of the arguments presented, showing how they were transformed during the period under study, and discusses their influence, or presence, in the diplomatic negotiations among the ambassadors of the United Provinces and the Catholic Monarchy in the German town of Münster. These discussions are inserted in the wider framework of a Christian realm that had to reassess its own values as a consequence of the confessionalisation process and the Thirty Years' War, which affected not only the Empire but, in one way or another, all Central and Western Europe